Assessment of Obstetric and Gynecological Nurses' Knowledge Regarding Water Birth in Mosul City: Penilaian Pengetahuan Perawat Obstetri dan Ginekologi Mengenai Persalinan Air di Kota Mosul - Rana Mohammed Jasim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Water birth has emerged as an alternative childbirth method that utilizes immersion in warm water to provide comfort for mothers and reduce stress during labor while maintaining physiological birth processes. Specific Background: Despite its potential benefits, the successful implementation of water birth in clinical settings largely depends on the knowledge and preparedness of healthcare professionals, particularly nurses working in obstetric units. Knowledge Gap: In Mosul city, limited empirical evidence exists regarding the knowledge level of obstetric and gynecological nurses concerning water birth practices and their clinical considerations. Aims: This study aimed to assess the knowledge level of obstetric and gynecological nurses regarding water birth and examine the relationship between knowledge and selected socio-demographic characteristics. Results: A descriptive cross-sectional study was conducted among 140 nurses working in obstetrics and gynecology departments in Mosul teaching hospitals using a structured questionnaire. The findings indicated that most nurses demonstrated an acceptable overall level of knowledge regarding water birth, while knowledge related to risks and indications requiring mothers to leave the water pool was frequently rated as not acceptable. Statistical analysis showed a significant association between nurses’ knowledge and their educational level as well as access to scientific sources. Novelty: This study provides one of the first empirical assessments of nurses’ knowledge regarding water birth practices in Mosul city. Implications: The findings highlight the need for improved educational programs, professional training, and greater access to scientific resources to strengthen nurses’ competencies in supporting safe water birth practices. Keywords: Water Birth, Nurses Knowledge, Obstetric Nursing, Maternal Care, Mosul Hospitals Key Findings Highlights Majority of participants demonstrated acceptable understanding of hydrotherapy childbirth concepts. Knowledge gaps identified in clinical risk recognition and maternal pool exit indications. Educational attainment and scientific reading associated with higher professional competency levels.